KAJIAN DAYA DUKUNG PONDASI BORED PILE BERDASARKAN DATA N-SPT, DATA RENCANA DAN PDA TEST (Studi Kasus : Pembangunan Jalan Tol Yogyakarta ”“ Bawen Seksi 1 Paket 1) - Junaidi, Junaidi; Supriyadi, Supriyadi; Larasati, Novita; Utama, Clara Arnindhita Sekar Wira Satya (Politeknik Negeri Semarang, 2024)
The bored pile foundation work at the locations of Kali Konteng, Sangu Banyu, and Kali Mataram in the Yogyakarta - Bawen Toll Road Construction Project Section 1 Package 1 exhibits differences in planned and actual (field) load-bearing capacity values. The aim of this study is to analyze the load-bearing capacity values of bored piles. This research utilizes secondary data in the form of planning data, PDA test results, and N-SPT data. Load-bearing capacity calculations are conducted using a conventional method with the Reese & Wright formula. The research findings reveal that the ultimate load-bearing capacity of cast-in-place concrete bored piles calculated based on N-SPT data using the Reese & Wright 1977 method is 1918.08 tons at the Kali Konteng location, 1532.34 tons at the Sangu Banyu location, and 1416.34 tons at the Kali Mataram location. Meanwhile, the planned load-bearing capacity at the Kali Konteng location is 1312.5 tons, at the Sangu Banyu location is 1175 tons, and at the Kali Mataram location is 1300 tons. At the abutment locations of Kali Konteng and Sangu Banyu, the load-bearing capacity values based on the PDA Test exceed the planned load-bearing capacity values but are smaller than the load-bearing capacity values calculated using the Reese & Wright method. Conversely, at the abutment location of Kali Mataram, the load-bearing capacity value determined by the PDA Test exceeds both the planned load-bearing capacity value and the load-bearing capacity value calculated using the Reese & Wright method.